Rediseño del Proceso de Desbaste del Tren de Laminación en Grupo Siderúrgico Reina GSR. (2022)
Some years ago, in Boyacá department the steelmarker sector had been stronger. It sector had more than 5 factories. In the GSR steelmarker the long steel production has increased annually. In each period of time the factory looks for being highly qualified and one on the best factories in Colombia and the world. During the production of this research project, we analized data related to the highly increase of long steel production. In this analysis we found a shortcoming in the polishing of rolling process in the Grupo Siderúrgico Reina of the factory. The main shortcoming was the the operation of the second and fourth horizontal boxes for vertical boxes. These boxes are going to avoid delays that's why it's not necessary the torsion of the lever. This could help to obtain a high quality products and minimize the steel waste.